# Extensions 1→N→G→Q→1 with N=C3×D4 and Q=C3×S3

Direct product G=N×Q with N=C3×D4 and Q=C3×S3
dρLabelID
S3×D4×C3272S3xD4xC3^2432,704

Semidirect products G=N:Q with N=C3×D4 and Q=C3×S3
extensionφ:Q→Out NdρLabelID
(C3×D4)⋊1(C3×S3) = C3×C327D8φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4):1(C3xS3)432,491
(C3×D4)⋊2(C3×S3) = C3×D4×C3⋊S3φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4):2(C3xS3)432,714
(C3×D4)⋊3(C3×S3) = C3×C12.D6φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4):3(C3xS3)432,715
(C3×D4)⋊4(C3×S3) = C32×D4⋊S3φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4):4(C3xS3)432,475
(C3×D4)⋊5(C3×S3) = C32×D42S3φ: trivial image72(C3xD4):5(C3xS3)432,705

Non-split extensions G=N.Q with N=C3×D4 and Q=C3×S3
extensionφ:Q→Out NdρLabelID
(C3×D4).1(C3×S3) = C3×D4.D9φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).1(C3xS3)432,148
(C3×D4).2(C3×S3) = C3×D4⋊D9φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).2(C3xS3)432,149
(C3×D4).3(C3×S3) = He38SD16φ: C3×S3/C32C2 ⊆ Out C3×D47212-(C3xD4).3(C3xS3)432,152
(C3×D4).4(C3×S3) = He36D8φ: C3×S3/C32C2 ⊆ Out C3×D47212+(C3xD4).4(C3xS3)432,153
(C3×D4).5(C3×S3) = Dic18⋊C6φ: C3×S3/C32C2 ⊆ Out C3×D47212-(C3xD4).5(C3xS3)432,154
(C3×D4).6(C3×S3) = D36⋊C6φ: C3×S3/C32C2 ⊆ Out C3×D47212+(C3xD4).6(C3xS3)432,155
(C3×D4).7(C3×S3) = C3×D4×D9φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).7(C3xS3)432,356
(C3×D4).8(C3×S3) = C3×D42D9φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).8(C3xS3)432,357
(C3×D4).9(C3×S3) = D4×C32⋊C6φ: C3×S3/C32C2 ⊆ Out C3×D43612+(C3xD4).9(C3xS3)432,360
(C3×D4).10(C3×S3) = C62.13D6φ: C3×S3/C32C2 ⊆ Out C3×D47212-(C3xD4).10(C3xS3)432,361
(C3×D4).11(C3×S3) = D4×C9⋊C6φ: C3×S3/C32C2 ⊆ Out C3×D43612+(C3xD4).11(C3xS3)432,362
(C3×D4).12(C3×S3) = Dic182C6φ: C3×S3/C32C2 ⊆ Out C3×D47212-(C3xD4).12(C3xS3)432,363
(C3×D4).13(C3×S3) = C3×C329SD16φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4).13(C3xS3)432,492
(C3×D4).14(C3×S3) = C9×D4⋊S3φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).14(C3xS3)432,150
(C3×D4).15(C3×S3) = C9×D4.S3φ: C3×S3/C32C2 ⊆ Out C3×D4724(C3xD4).15(C3xS3)432,151
(C3×D4).16(C3×S3) = C32×D4.S3φ: C3×S3/C32C2 ⊆ Out C3×D472(C3xD4).16(C3xS3)432,476
(C3×D4).17(C3×S3) = S3×D4×C9φ: trivial image724(C3xD4).17(C3xS3)432,358
(C3×D4).18(C3×S3) = C9×D42S3φ: trivial image724(C3xD4).18(C3xS3)432,359

׿
×
𝔽